SAT0160 Coronary and Abdominal Aorta Calcification in Rheumatoid Arthritis: Relationships with Traditional Cardiovascular Risk Factors, Disease Characteristics and Concomitant Treatments. (10th June 2014) - Paccou, J.; Renard, C.; Liabeuf, S.; Kamel, S.; Fardellone, P.; Massy, Z.; Brazier, M.; Mentaverri, R.
Abstract : Background: Patients with rheumatoid arthritis (RA) are exposed to accelerated atherosclerosis and a substantially elevated risk of cardiovascular events (especially coronary heart disease) and death. However, this morbi-mortality cannot be fully explained by traditional cardiovascular risk factors. A growing body of evidence suggests that non-traditional cardiovascular risk factors such as chronic inflammation, the disease characteristics and concomitant treatments have a pivotal role in accelerated atherosclerosis and the increased cardiovascular disease risk in patients with RA. Vascular calcification is commonly used as a subclinical marker of atherosclerosis and has been linked to increased all-cause mortality, cardiovascular mortality and coronary events. Objectives: The present study assessed the influence of traditional cardiovascular risk factors, disease characteristics and concomitant treatments in patients with RA on coronary artery calcification (CAC) and abdominal aorta calcification (AAC). Methods: In a cross-sectional study, 75 patients with RA were compared with 75 age- and gender-matched control participants. The CAC and AAC scores were measured by computed tomography in patients who were free of coronary artery disease. The relationships between the presence or absence of CAC and AAC and traditional cardiovascular risk factors, disease characteristics and concomitant treatments in patients with RA were assessed in a multiple logistic regression analysis. Results: RA and control groups did not differ significantly in terms of age, gender composition or the prevalence of traditional cardiovascular risk factors. Coronary artery calcification was more prevalent in patients with RA (65.3%) than in controls (49.3%) (p=0.04). The mean CAC score was 197±470 in patients with RA and 109±297 in controls (p=0.07). AAC was also more prevalent in patients with RA (71.2%) than in controls (54.7%) (p=0.04). The mean AAC score was 1.0±1.3 in patients with RA and 0.7±1.4 in controls (p=0.02). Older age (OR=1.15; p<0.01), hypertension (OR=3.77; p=0.04) were found to be independently associated with CAC, whereas current use of methotrexate (OR=0.12; p=0.01) was found to be associated with the absence of CAC. Older age (OR per year=1.17; p<0.001) and erosive arthritis (OR=3.78; p=0.03) were found to be independently associated with AAC. Conclusions: This study demonstrates for the first time that in patients with RA, (i) AAC is more prevalent and more severe compared with age- and gender-matched control participants (ii) current use of methotrexate is a major determinant of the absence of CAC and (iii) erosive arthritis is a major determinant of AAC. References: Paccou J, Brazier M, Mentaverri R, et al. Vascular calcification in rheumatoid arthritis: prevalence, pathophysiological aspects and potential targets. Atherosclerosis 2012;224:1418-23. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1609